(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The higher educational institutions (HEIs) of developing countries have two most important challenges i.e. cost effective ICT solutions, aligning ICTs with modern technologies and adopt sustainable approaches to significantly reduce the power consumption. An essential aim of the paper is to determine how to reduce power consumption & carbon foot prints, apply reduce, reuse and recycle practices for ICT equipment’s in HEIs. The developing country like Ethiopia is one of the countries where power scarcity is a big challenge and required to develop strategies that can encourage power savings along with green ICT strategies. Developing countries also face numerous challenges like strategic alignment in energy efficient techniques, refurbishing, reusing and recycling of the ICT equipment with standard scientific practices. Developing continent countries like African HEIs are still reluctant in adopting the energy efficiency standards practices. As a primary observation, it was observed that these HEIs are still away from the wide range adoption of energy efficient mechanism and green standard practices for ICT equipment. This research paper analyzed the current green ICTs usage in HEIs and selected three universities as sampling sites for primary data collection, case observation, and analysis. Finally a green ICT framework for reducing power consumption, reusing, refurbishing and recycling the ICT equipment in HEIs is proposed for adoption. The research performed experimental analysis in simulated environment using dynamic voltage and frequency scaling technique (DVFS) with VM migration. The simulated results found that the total consumption of energy by the ICT center is approximately reduced by 95 % for the specified configuration of the ICT center equipment. The results showed the significant contribution to reduce energy consumption, minimize environmental impacts and reduce the Co2 emission especially in the selected university ICTs.